Workers' Participation in Europe: Challenges facing the European policy of the European Parliament and the European Commission for 2014 and subsequent years - Sebastian Sick; Oliver Emons; Norbert Kluge; Lasse Pütz; Marion Weckes; Aline Hoffmann (Hans-Böckler-Stiftung, 2014)
- The economic and financial crisis has raised questions about the meaning and purpose of corporate governance. After the manifest failure of the economic-liberal "shareholder value" model, a new model of "good corporate governance" deserves a closer look. How can this be optimally backed up and embedded in European company law, as well as in the European Directives on employee involvement? - In 18 of the 28 EU Member States, employee participation in top-level management is provided for by law. In 12 EU Member States and in Norway, these practices are widespread. Workers' participation at company board level is a core component of European company law, and information and consultation are basic rights in a social Europe. - European policy must pay attention to protecting, strengthening and further developing workers' rights in the interest of enhancing Europe in the eyes of its citizens and for the sake of its economy. There should be no loopholes that make it possible to circumvent workers' participation.
Keywords: 330